3D model related to the publication: A new cynodont from the Upper Triassic Los Colorados Formation (Argentina, South America) reveals a novel paleobiogeographic context for mammalian ancestors - Gaetano, Leandro Carlos (2022)
The present 3D Dataset contains the 3D model analyzed in Gaetano, L. C., Abdala, F., Seoane, F. D., Tartaglione, A., Schulz, M., Otero, A., Leardi, J. M., Apaldetti, C., Krapovickas, V., and Steinbach, E. 2021. A new cynodont from the Late Triassic Los Colorados Formation (Argentina, South America) reveals a novel paleobiogeographic context for mammalian ancestors. Scientific Reports.